Analysis of neural stem cell self-renewal and differentiation using in vivo RNAi in drosophila. - Wong, Jian Xiang. (2010)
Drosophila neural stem cells, larval brain neuroblasts, have recently emerged as a new model for the study of stem cells self-renewal and differentiation. This delicate balance is achieved through asymmetric division of neuroblasts. The factors that are required for self-renewal or differentiation are localized asymmetrically and segregated into different daughter cells during neuroblast divisions. Failure of asymmetric division of neuroblasts can result in over-proliferation resembling tumor formation or abnormal brain development. In this study, we screened a collection of 500 RNAi lines and identified a number of mutants in the process. Given the conserved molecular mechanisms of asymmetric divisions between fly and mammals, our study will greatly contribute to a better understanding of neural stem cells self-renewal and differentiation during mammalian neurogenesis as well as tumorigenesis.